PENERAPAN MENYAMA BRAYA DALAM KOMUNIKASI SOSIAL UNTUK MENINGKATKAN IKLIM KERJA DI URBANLIFE STORE BALI - Suratningtyas, Luh Putu Ega; Segara, I Nyoman Yoga; Dasih, I Gusti Ayu Ratna Pramesti (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Conducive work climate creates a strong basis for relationships between employees that support overall company achievements. In order to support the work climate, Urbanlife Store Bali implements social communication based on menyama braya, the concept encourages employees to help each other, build harmony and kinship. This research aiming to explain the reasons for menyama braya being a basis for social communication in supporting the work climate, find out the application of menyama braya and describe the implications. Theories that used are interaction adaptation theory, communication accommodation theory and social action theory. Research was located at the Urbanlife Store Bali. With qualitative type of research and also determining informants using the purposive sampling method. Data was collected through interviews, observation and literature study. The reason menyama braya used as a basis of social communication at Urbanlife Store Bali are to build cooperation between employees, create principles of equality and diversity, and prevent tension between employees. The implementations of menyama braya are introducting culture; cooperation in completing work; tolerance for differences in tenant operating hours; mutual trust, flexibility and employee involvement in decision making; celebrating employee special days and giving rewards; suka-duka activities and adjustments of evaluation methods. Last, implications are viewed from cognitive, affective, and behavioral aspect.